2000
DOI: 10.1063/1.1331084
|View full text |Cite
|
Sign up to set email alerts
|

High-quality p–n junctions with quaternary AlInGaN/InGaN quantum wells

Abstract: We report on quaternary AlInGaN/InGaN multiple quantum well (MQW) light emitting diode structures grown on sapphire substrates. The structures demonstrate high quality of the p–n junctions with quaternary MQW. At low forward bias (below 2 V), the temperature dependent of current–voltage characteristics are exponential with the ideality factor of 2.28, which is in a good agreement with the model of the injected carrier recombination in the space charge region. This ideality factor value is approximately three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 10 publications
3
52
1
Order By: Relevance
“…The large value of ideality factor (42) implies that the tunneling mechanism dominates the carrier transport in the 310 nm LEDs rather than the diffusion or the space charge recombination process. The possible tunneling mechanisms include carriers that tunnel into as well as out of active region directly and/or via intermediate states present within the energy gap [9][10][11][12][13]. The latter mechanism is especially significant due to presence of the high density of impurities as well as dislocations in the nitride semiconductors, particularly the p-type layer [11,12].…”
Section: Resultsmentioning
confidence: 98%
“…The large value of ideality factor (42) implies that the tunneling mechanism dominates the carrier transport in the 310 nm LEDs rather than the diffusion or the space charge recombination process. The possible tunneling mechanisms include carriers that tunnel into as well as out of active region directly and/or via intermediate states present within the energy gap [9][10][11][12][13]. The latter mechanism is especially significant due to presence of the high density of impurities as well as dislocations in the nitride semiconductors, particularly the p-type layer [11,12].…”
Section: Resultsmentioning
confidence: 98%
“…This flexibility allows the lattice strain of heterostructures ͑e.g., InGaN quantum wells with AlInGaN barriers͒ to be varied between compressive, zero, and tensile strain. Enhanced crystal quality has been observed in quantum heterostructures of AlInGaN/InGaN, 11,12 and the piezoelectric field produced by the strain was eliminated 13 by using lattice matched AlInGaN/InGaN templates.…”
Section: Introductionmentioning
confidence: 98%
“…Unrealistic ideality factors of 4-6 in these devices were observed. Recently, Chitinis et al [5] demonstrated a high-quality AlInGaN/InGaN multiple quantum well (MQW) LED structure by incorporation of a small amount of In into the AlGaN barrier layers. The electrical characteristics showed an ideality factor of 2.28, which was close to the theoretical prediction for carrier recombination in the space-charge region.…”
Section: Introductionmentioning
confidence: 99%